Managing Hyperprogressive Disease in the Era of Programmed Cell Death Protein 1/Programmed Death‐Ligand 1 Blockade: A Case Discussion and Review of the Literature. (24th February 2020) - Grecea, Miruna; Marabelle, Aurélien; Ammari, Samy; Massard, Christophe; Champiat, Stéphane
Abstract: : A breakthrough in oncology over the last 5 years, immunotherapy has proved its salutary effects in a wide range of solid tumors. The targeting of the programmed cell death protein 1 (PD‐1)/programmed death‐ligand 1 (PD‐L1) pathway can restore a competent antitumor T‐cell response by addressing key tumor immune evasion mechanisms. This novel mechanism of action is associated with new patterns of responses that were not observed with conventional treatments such as chemotherapy or targeted therapies. Thus, hyperprogressive disease (HPD), an unexpected acceleration of cancer evolution after starting immunotherapy, has been reported by several groups with a PD‐1/PD‐L1 blockade. This tumor flare‐up phenomenon is associated with a poorer outcome and is suspected to be an immune‐related adverse event. Despite been highly debated, the issue of HPD is currently a real challenge for oncologists' practice in terms of patients' information, diagnosis, and management. Herein, we describe the case of a 57‐year‐old man diagnosed with metastatic urothelial carcinoma who developed a rapid tumor growth after an anti‐PD‐L1+ IO combination. This case illustrates how current practice should evolve to address the HPD reality in the anticheckpoint era. Key Points : Hyperprogressive disease (HPD) is an unexpected acceleration of cancer growth after starting immunotherapy that is associated with a poor outcome. Definition of HPD is based on comparing kinetics of tumor growth before and after starting immunotherapy. No predictive biomarker has been homogenously identified in the reported studies. Suspected pathophysiology includes expansion of programmed cell death protein 1 (PD‐1) + regulatory T cells, exhaustion of compensatory T cells, modulation of pro‐tumorigenic immune cell subsets, activation of aberrant inflammation, or activation of oncogenic signaling. HPD is one of the most controversial immune‐related adverse events, as the liability of immunotherapy in this tumor deleterious flare‐up phenomenon has not been proved yet. The reported incidence of HPD in retrospective studies varies across different solid tumor types from 6% to 29%. This phenomenon has been mainly suspected in non‐small cell lung cancer (NSCLC), head and neck squamous cell carcinoma (HNSCC), and in urothelial carcinomas, where several randomized phase III trials have shown early crossing over of survival curves. In the context of anti‐PD‐1/programmed death‐ligand 1 therapy, in particular for NSCLC, HNSCC, or urothelial carcinoma, the authors recommend performing an early computed tomography (CT) assessment at week 3–4. In the case of an early progression, tumor molecular characterization by tumor biopsy or circulating tumor DNA could be urged. Immunotherapy discontinuation should be discussed. Performing a confirmatory CT scan 4 weeks later to exclude pseudoprogression should not be the rule. Early switch to cytotoxic therapy may counteract the deleterious flare‐up. Patients should be informed of the risk of developing HPD. Health authorities and trial sponsors could monitor and report the rates of tumor flares in trials in order to help oncologists to properly inform their patients about the expected rates of HPD. Abstract : Hyperprogressive disease, an unexpected acceleration of cancer evolution after starting immunotherapy, has been reported with PD‐1/PD‐L1 blockade treatment. This case report describes a patient diagnosed with metastatic urothelial carcinoma who developed a rapid tumor growth after anti‐PD‐L1 combination treatment.